Eating Less to Impress? The Influence of Cross-Gender Presence and Impression Management on Portion Sizes among Undergraduate Students - Gracia Pramudita; Undarwati, Anna (Jurnal Promkes: The Indonesian Journal of Health Promotion and Health Education, 2025)
Background: Data from the RISKESDAS year 2018 indicates an increasing prevalence of overweight among adults. This increase is in line with the increase in portion sizes, where the presence of people of different gender and impression management are suspected to influence portion sizes. Hence, further study on portion sizes is needed to aid in developing effective policies to promote healthy eating behaviors. Objectives: To investigate the influence of cross-gender presence and impression management on portion sizes during lunch. Method: This study employed a quasi-experimental design consisting of control and experimental groups. The experiment involved a confederate as a dining companion for participants in the experimental group whose gender differs from the participants. We analyzed data from 227 participants, with an expected effect size of d = 0.25, significance level (α) of 0.05, and power of 0.95. Participant criteria included being students of Universitas Negeri Semarang (UNNES), not currently on a diet, having no allergies, and not being vegan or vegetarian. Impression management was measured using items from Turnley & Bolino (1999), while portion sizes were measured using the Fake Food Buffet (FFB) developed by Bucher et al. (2011). Results: Participants with high impression management tended to have larger portion sizes when dining with individuals of the opposite gender than when dining alone. Impression management positively influenced portion sizes. Without the influence of impression management, when dining with individuals of the opposite gender, participants tended to choose smaller portion sizes compared to when dining alone. Conclusion: The community must be aware of the significant influence of high impression management and the presence of individuals of the opposite gender on meal portions. Individuals with high impression management may consider avoiding social eating situations if they want to reduce their portion sizes.